RETENTION AND LIPOPHILICITY OF ESTRADIOL DERIVATIVES IN NORMAL- AND REVERSED-PHASE HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - Ačanski, M.; Vujić, Đ.; Nježić, Z. (Journal of Engineering & Processing Management, 2012)
The retention behaviour and separation ability of some estradiol derivatives were studied by HPLC on silica and C-18 commercially available columns. The mobile phases used were: benzene-ethyl acetate, benzene-tetrahydrofuran, benzene-acetonitrile, isopropanol-water and tetrahydrofuran-water in various proportions. The results are discussed in terms of nature of the solute, eluent and stationary phase. Correlation between the retention constants of estradiol derivatives obtained on C-18 column and log P calculated by program ACD log P was examined too.